Pear flower and leaf microbiome dynamics during the naturally occurring spread of Erwinia amylovora - Aia Oz; Orly Mairesse; Shira Raikin; Hila Hanani; Hadar Mor; Mery Dafny Yelin; Itai Sharon (mSphere)
ABSTRACT Erwinia amylovora is the causal pathogen of fire blight, a contagious disease that affects apple and pear trees and other members of the family Rosaceae. In this study, we investigated the community dynamics of the pear flower microbiome in an agricultural setting during the naturally occurring infection of E. amylovora. Five potential factors were considered: collection date, the flower's phenological stage, location on the tree, location within the orchard, and pear cultivar. The phenological stage and the collection date were identified as the most important factors associated with pear flower microbiome composition, while the location of the tree in the orchard and the flower's location on the tree had a marginal effect. The leaf microbiome reflected that of the abundant phenological stage on each date. The flower microbiome shifted toward E. amylovora dominating the community as time and phenological stages progressed, leading to a decreased community diversity. The E. amylovora population was represented almost exclusively by six amplicon sequence variants (ASVs) with similar proportions throughout the entire collection period. Other taxa, including Pseudomonas, Pantoea, Lactobacillus, and Sphingomonas, were represented by dozens of ASVs, and different succession patterns in their populations were observed. Some of the taxa identified include known antagonists to E. amylovora. Overall, our results suggest that flower physiology and the interaction with the environment are strongly associated with the pear flower microbiome and should be considered separately. Taxon-specific succession patterns under E. amylovora spread should be considered when choosing candidates for antagonist-based treatments for fire blight.IMPORTANCEThe spread of pathogens in plants is an important ecological phenomenon and has a significant economic impact on agriculture. Flowers serve as the entry point for E. amylovora, but members of the flower microbiome can inhibit or slow down the proliferation and penetration of the pathogen. Knowledge about leaf and flower microbiome response to the naturally occurring spread of E. amylovora is still lacking. The current study is the first to describe the Rosaceae flower microbiome dynamics during the naturally occurring infection of E. amylovora. Unlike previous studies, the study design enabled us to evaluate the contribution of five important environmental parameters to community composition. We identified different ASV succession patterns across different taxa in the flower consortia throughout the season. These results contribute to our understanding of plant microbial ecology during pathogen spread and can help improve biological treatments for fire blight.